An FPGA Based Controller for a SOFC DC-DC Power System. (28th December 2013) - Bhuyan, Kanhu Charan; Sao, Sumit Kumar; Mahapatra, Kamalakanta
Abstract : Fuel cells are an attractive option for alternative power and of use in a variety of applications. This paper proposes a state space model for the solid oxide fuel cell (SOFC) based power system that comprises fuel cell, DC-DC buck converter, and load. In this investigation we have taken up a case study for SOFC feeding a DC load where a DC-DC buck converter acts as the interface between the load and the source. A proportional-integral (PI) controller is used in conjunction with pulse width modulation (PWM) that computes the pulse width and switches the MOSFET at the right instant so that the desired voltage is obtained. The proposed model is validated through extensive simulation using MATLAB/SIMULINK. Controller for the fuel cell power system (FCPS) is prototyped using XC3S500E development board containing a SPARTAN 3E Xilinx FPGA that simplifies the entire control circuit besides providing additional flexibility for further improvement. The results clearly indicate improved performance and validate our proposed model.